2001
DOI: 10.1152/ajpheart.2001.280.6.h2554
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of involvement of GIRK1/GIRK4 in long-term desensitization of cardiac muscarinic K+channels

Abstract: The cardiac M2 muscarinic receptor/G protein/K+ channel system was studied in neonatal rat atrial cells cultured with and without 10 microM carbachol (CCh) for 24 h. Channel activity in CCh-pretreated cells was substantially reduced as a result of long-term desensitization regardless of whether the channel was activated by ACh in cell-attached patches or GTP in inside-out patches. Channel activity in CCh-pretreated cells was also low when the receptor was bypassed and the G protein and channel were directly ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…1 and 2). The first time constant compares well with previous measurements of the time constant of desensitization of I K,ACh , e.g., 2.5 min in guinea pig atrial cells (38) and 1.2 min in rabbit sinoatrial node cells (12), and the second time constant corresponds to a much slower process of desensitization of I K,ACh described by Bünemann et al (3) and Shui et al (30,32). Internalization of the M 2 receptor was equally as rapid: under similar conditions, M 2 -receptor labeling in the cell membrane declined by ϳ83% over a double-exponential time course with time constants of 2.9 Ϯ 1.7 and 51.8 Ϯ 26.3 min (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…1 and 2). The first time constant compares well with previous measurements of the time constant of desensitization of I K,ACh , e.g., 2.5 min in guinea pig atrial cells (38) and 1.2 min in rabbit sinoatrial node cells (12), and the second time constant corresponds to a much slower process of desensitization of I K,ACh described by Bünemann et al (3) and Shui et al (30,32). Internalization of the M 2 receptor was equally as rapid: under similar conditions, M 2 -receptor labeling in the cell membrane declined by ϳ83% over a double-exponential time course with time constants of 2.9 Ϯ 1.7 and 51.8 Ϯ 26.3 min (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Although the results from the present study suggest that slow desensitization of I K,ACh is largely the result of the M 2 receptor, other possible factors cannot be excluded. Our group (32) has previously shown that, after a 24-h exposure to 10 M CCh, activity of the ACh-activated K ϩ channel in rat atrial cells is greatly reduced even if the M 2 receptor is bypassed and the channel is activated directly by GTP␥S (32). This suggests that, as well as the receptor, the G protein and/or the channel is altered during the desensitization process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that Kir3 channel cell membrane expression is regulated by both G-proteins and endocytosis via activation of the GPCR. Trafficking of the Kir3 channel with the muscarinic receptor was unexpected; for example, carbachol stimulation of muscarinic receptors in atrial myocytes decreased levels of surface receptors but not Kir3.1/3.4 channels (Shui et al, 2001). A similar mechanism of dual regulation of N-type voltage-gated Ca 2ϩ channels and opioid receptor-like receptors 1 was recently reported; agonist stimulation triggered the vesicular internalization of the both the receptor and Ca 2ϩ channel in rat dorsal root ganglion cells, providing a key mechanism for regulating Ca 2ϩ channel activity (Altier et al, 2006).…”
Section: Implications Of Sequestered Gpcr/kir3 Channel Signaling Compmentioning
confidence: 99%